Electrify : an optimist's playbook for our clean energy future - Griffith, Saul (The MIT Press, 2021)
"Saul Griffith lays out an accessible, rigorously-researched plan to decarbonize the U.S. economy in time to address climate change. His plan, in short, is to "electrify everything." Griffith uses his deep understanding of U.S. energy flows, materials, and clean energy technologies to show that decarbonizing in time to meet climate goals is not only possible, but can be done without major sacrifices in our lifestyles, creating more jobs and a cleaner, healthier environment. Unlike many books in the climate space, Griffith's Electrify is optimistic, drawing on historical precedents to show that we are up for meeting the challenge of global warming-if we act decisively, and fast"--